(untitled) (Fiep Bulletin - online, 2016)
The first year of the infant’s life is essential to start a healthy and adequate food, preventing infant death and disease in this stage of life as well as in adulthood. This study aimed to analyze the knowledge acquired by community health agents (CHA) of the city of Macaé in training on infant feeding. This is a descriptive, quantitative study of primary basis with data from a training course on breastfeeding and complementary feeding returned to CHA, in collaboration with the Basic Attention Management Macaé. The training took place in a turn of the week, in February 2015, containing the following schedule: opening, applying a pre-test to observe the existing knowledge on the subject; Lectures: "Physiological aspects of the infant" with "Breastfeeding" and "timely and safe complementary feeding". At the end, there were one QUIZ and a post-test to evaluate the acquired knowledge. Fifty on CHA were trained, of these 96.1% (n=49) answered the questionnaire in the pre-test and 100% in the post-test. In the pre-test, 71.4% of CHA presented a percentage of correct answers above 50%; and the successes were mainly on breastfeeding. Of those who hit less than half of the questions (28.6%) were found to be complementary feeding with the lowest proportion of correct answers. After the training, the post-test, it was found that the majority of CHA has improved the proportion of correct answers: 92.2% got more than half of the questions, and only 7.8% got less than half of the questions on the form. It was concluded that training increased knowledge about infant feeding mainly complementary feeding.